Zinc Oxide Nanoparticles in Modern Science and Technology: Multifunctional Roles in Healthcare, Environmental Remediation, and Industry - Veeranjaneya Reddy Lebaka; Perugu Ravi; Madhava C. Reddy; Chandrasekhar Thummala; Tapas Kumar Mandal (Nanomaterials)
Zinc oxide nanoparticles (ZnO NPs) have garnered significant attention across various scientific and technological domains due to their unique physicochemical properties, including high surface area, photostability, biocompatibility, and potent antimicrobial activity. These attributes make ZnO NPs highly versatile, enabling their application in biomedicine, environmental science, industry, and agriculture. They serve as effective antimicrobial agents in medical treatments and as catalysts in environmental purification processes, owing to their ability to generate reactive oxygen species (ROS) and exhibit photocatalytic activity under UV light. Moreover, ZnO NPs are being increasingly employed in advanced drug delivery systems and cancer therapies, highlighting their potential in modern medicine. Their growing popularity is further supported by their ease of synthesis, cost-effectiveness, and capacity for diverse functionalization, which expand their utility across multiple sectors. This review focuses on research from the past five years (2020–2025) on the practical uses of ZnO nanoparticles in the biomedical, environmental, industrial, and agricultural fields. It also highlights current trends, existing challenges, and future perspectives. By examining these aspects, the article provides a comprehensive understanding of the versatile roles of ZnO NPs and their emerging significance in science and technology.